Individual and combinatory effects of voluntary wheel running and sActRIIB-Fc administration on redox-balance in mdx mice - Hentilä, Jaakko (2015)
Duchenne’s muscular dystrophy (DMD) is X-chromosome linked muscle wasting dis-ease. It is caused by a mutation in the gene coding protein called dystrophin leading to premature death and significantly impairing the quality of life of DMD patients. Oxida-tive stress is a contributing factor in the pathology of DMD. Light intensity exercise and interventions that promote sirtuin (SIRT) 1 activity have been shown to be antioxidant for mdx mice and to ameliorate the symptoms of DMD. Also blocking activin receptor IIB (ActRIIB) ligands has been shown in some, but not all studies to improve the pa-thology of the DMD. The purpose of this study was to find out the individual and com-binatory effects of voluntary wheel running and blocking ActRIIB ligands with soluble fusion protein of ActRIIB (promotes muscle hypertrophy)(sActRIIB-Fc) on redox bal-ance in mdx mice, an animal model for Duchenne’s muscular dystrophy. The mdx mice were randomly divided into 4 groups (n=8 in each): PBS placebo sedentary, PBS place-bo running, sActRIIB-Fc administered sedentary, and sActRIIB-Fc administered run-ning group. In addition, wild-type PBS placebo treated mice served as a control group. sActRIIB-Fc was injected intraperitoneally, once a week for 7 weeks, which was also the length of the intervention period. Mice in the running groups had free access to run-ning wheels. Redox balance was assessed by measuring the amount of oxidized (GSSG) and reduced glutathione (GSH) in the gastrocnemius muscle. Outcome of the redox bal-ance i.e oxidative damage was assessed from the carbonylated proteins using western immunoblot analysis. Furthermore, protein expression of SIRT1, the phosphorylation of SIRT1 at ser 46 (p-SIRT1), SIRT3, SIRT6, AMPK, and the phosphorylation of AMPK at thr 172 (p-AMPK) were measured using western immunoblot analysis. There was in-creasing running effect in the oxidized glutathione (GSSG) (p=0.014), increasing run-ning effect in the ratio of the oxidized glutathione and total glutathione (GSH/TGSH) (p=0.012), increasing running effect in the ratio of oxidized glutathione and reduced glutathione (GSSG/GSH) (p=0.0006) and increasing running effect in protein carbonyls (p=0.026) (2x2 ANOVA). In addition, there was increasing running x sActRIIB-Fc in-teraction effect in the carbonylated proteins (p=0.018), increasing running x sActRIIB-Fc interaction effect in p-SIRT1 (p=0.025) and increasing running x sActRIIB-Fc inter-action effect and in the ratio of p-AMPK and AMPK (p-AMPK/AMPK) (p=0.029) (2x2 ANOVA). However, there were no changes in SIRT1, 3 and 6 protein expressions. The main finding of this study was that combination of exercise and blocking ActRIIB binding ligands with sActRIIB-Fc increased protein carbonyls which was accompanied by increased phosphorylation of SIRT1 at ser 46 and oxidized form of glutathione (GSSG). In addition running independently increased protein carbonyls and oxidized glutathione. These results suggest that voluntary wheel running independently and combined with sActRIIB-Fc administration results in elevated oxidative stress that dystrophic mice can’t fully rescue with endogenous antioxidants.